CloudSat‐Inferred Vertical Structure of Snowfall Over the Antarctic Continent. Issue 2 (20th January 2020) - Lemonnier, F.; Madeleine, J.‐B.; Claud, C.; Palerme, C.; Genthon, C.; L'Ecuyer, T.; Wood, N. B.
Abstract: Current global warming is causing significant changes in snowfall in polar regions, directly impacting the mass balance of the ice caps. The only water supply in Antarctica, precipitation, is poorly estimated from surface measurements. The onboard cloud‐profiling radar of the CloudSat satellite provided the first real opportunity to estimate solid precipitation at continental scale. Based on CloudSat observations, we propose to explore the vertical structure of precipitation in Antarctica over the 2007–2010 period. A first division of this data set following a topographical approach (continent vs. peripheral regions, with a 2, 250 m topographical criterion) shows a high snowfall rate (275 mm · yr − 1 at 1, 200 m above ground level) with low relative seasonal variation ( ± 11 % ) over the peripheral areas. Over the plateau, the snowfall rate is low (34 mm · yr − 1 at 1, 200 m above ground level) with a much larger relative seasonal variation ( ± 143 % ). A second study that follows a geographical division highlights the average vertical structure of precipitation and temperature depending on the regions and their interactions with topography. In particular, over ice shelves, we see a strong dependence of the distribution of snowfall on the sea ice coverage. Finally, the relationship between precipitation and temperature is analyzed and compared with a simple analytical relationship. This study highlights that precipitation is largely dependent on the advection of air masses along the topographic slopes with an average vertical wind of 0.02 m · s − 1 . This provides new diagnostics to evaluate climate models with a three‐dimensional approach of the atmospheric structure of precipitation. Key Points: Regridding of the CloudSat observations reveals the 3‐D structure of solid precipitation over Antarctica Distributions vary substantially by type of region: ice sheet, peninsula, or ice shelves Precipitation rate‐temperature relationship is explained by large‐scale orographic snowfall